Novel data detection and channel estimation methods for coded and uncoded CPM signals - Wang, Wenwen (2014)
Bandwidth limitations and cost considerations are important criteria in mobile communication system developments and these have motivated considerable investigations into continuous phase modulation (CPM) techniques. In recent years, the higher frequency bands have been widely used due to the bandwidth limitations. Thus, fading rates are increasing as the fading rate is proportional to the carrier frequency. Therefore, in modern communication systems, reliable data detection under channels with considerable fading rates poses challenging research problems. In wireless communications, the transmitted signal is usually affected not only by additive white gaussian noise (AWGN) but also by channel fading. Coding is a typical way to combat fading. The combination of coding with CPM achieves performance gains and bandwidth efficiency at the same time. In order to obtain reliable communication, channel estimation is necessary. Therefore, in this thesis joint data detection and channel estimation schemes are investigated for coded and uncoded CPM signals. At first data detection for CPM signals transmitted over an AWGN channels is presented. A robust phase estimation based symbol detection algorithm, which does not require the recovery of the modulation index and the alphabet size, is proposed for M-ary full response CPM signals. Secondly, a novel joint data detection and channel estimation algorithm is proposed for CPM signals transmitted over a time-varying flat fading channel. The proposed algorithms mentioned above provide hard outputs only, and therefore, is not suitable for an iterative receiver which needs soft input soft output (SISO) modules. Thus, thirdly, the hard output module is extended to a novel adaptive SISO module for serially concatenated CPM (SCCPM) signals transmitted over a frequency flat fading channel. Finally, joint data detection and channel estimation for an orthogonal space-time block coded CPM system is investigated. Two objectives are considered: preserving the bandwidth efficiency at the transmitter and the accuracy of data detection at the receiver. It is worth noting that channel estimation problem of orthogonal space-time block coded CPM has not been previously taken into consideration in the literature. Throughout the thesis, extensive simulation results are provided to validate the effectiveness of the proposed algorithms.